Making the links among environmental protection, process safety, and industry 4.0 - Gobbo, Jose Alcides [UNESP]; Busso, Christianne M. [UNESP]; Gobbo, Simone Cristina O. [UNESP]; Carreão, Henrique [UNESP] (Elsevier, 2018)
Industry 4.0 is an emerging concept in production systems and is described as a concept that encompasses technologies such as the Internet of Things, big data, cyber-physical systems, and smart objects. Industry 4.0 will present new challenges and opportunities for process safety and environmental protection (PSEP) researchers and managers. There is a gap in the literature in identifying the main concepts related to industry 4.0 and PSEP, as well as the potential integration between these subjects. In line with this gap, this paper focuses on identifying and systemizing information regarding the integration of PSEP and industry 4.0 concepts and technologies. While identifying relationships, we also address non-existent intersections between keyword co-occurrence networks in PSEP and industry 4.0. The main outputs of this research are: (a) identification and discussion of potential connections between PSEP with industry 4.0 concepts; and (b) an in-depth discussion of potential benefits in integrating industry 4.0 concepts and technologies into PSEP fields. It can be concluded that there is much more collaborative research between environmental protection and industry 4.0 than between process safety and industry 4.0. Also, environmental protection research is characterized by a wide variety of research themes and multidisciplinary endeavours, in contrast with industry 4.0.
Keywords: Bibliometric networks; Environmental protection; Industry 4.0; Process safety